FAKTOR-FAKTOR PENDUKUNG KEBAHAGIAAN PADA EMPAT NARAPIDANA WANITA DI LAPAS WANITA KELAS II A - Natanael Lewi; Shanty Sudarji (Psibernetika, 2015)
Inmates have a great potential to generate pressures that make them unhappy. This can lead to stress and tend to have a desire to commit suicide. To minimize this they need the ability to look for happiness in order to reduce the negative impact arising from the situation in prisons. There are two factors that affect happiness is internal and external factors. Internal factors, there are 3 (three), namely the satisfaction of the past, optimism about the future, and happiness in the present. External factors are 5 (five), namely social life, religion or religiosity, marriage, money and health. This study used qualitative techniques in analyzing the data. Data were obtained through interviews and observations. The number of research subjects are four people according to specified criteria. The results showed on the subject C supporting factors of happiness comes from internal and external factors likely to be achieved, on the subject W and D tend to be achieved on the factors supporting the happiness derived from external factors alone. On the subject of A tends not achieved the supporting factors of happiness derived from external and internal factors. The conclusion from this study is only one subject that is the subject of C which tends achieved in supporting factors of happiness derived from external and internal factors, the remaining three subjects achieved only on external happiness factors alone, or internal only. If the views of external and internal factors supporting factors of happiness, of 4 subjects only 3 subjects tend to be achieved in the happiness of external factors, while the source of happiness internal factors, of 4 subjects only one subject that tends to be achieved.Keywords: Happiness, Women Prisoners